COMMUNITY PERCEPTIONS OF URBAN TRANSPORT PERFORMANCE - Prima Jiwa Osly; Wita Meutia; Erlangga Darmawan (Jurnal Infrastruktur, 2023)
Angkutan Kota or commonly called “Angkot” is one of the public transportation that is often found in Bogor. One of the Angkot routes in Bogor is Angkot 03 in the Bubulak-Baranangsiang route. This public transportation has a bad category for the service performance dimension with a poor category. This can be seen from public transportation services such as passenger volume, distance traveled, and stopping at any place to look for passengers. With services in the deficient category, it can reduce people's interest in using public transport in this direction, both for existing users and potential potential users. Therefore, it is necessary to pay attention to the satisfaction of users and the satisfaction of the community around the public transportation route towards public transportation in this direction. The aim of this research is to determine the performance of public transportation services based on the perceptions of public transportation users and the surrounding community. Data from this research were obtained from distributing questionnaires to passangers of Angkot 03 in the Bubulak - Baranangsiang route and people living around the public transportation route. The results of the questionnaire were analyzed using the IPA method to determine the gap between expectations and performance of public transportation services. Based on the results of the analysis, it can be seen that there are the same variables that need to be improved between the perceptions of city transport passengers and the surrounding community, namely variable 12 (Drivers are courteous, kind, and doesn’t smoke).